Strategi Retorika Krisis Pejabat Publik dalam Mengelola Opini asyarakat: Analisis Framing di Tiga Media Online Indonesia: Studi Kasus Pernyataan Menteri Komunikasi dan Informatika dalam Kasus Korupsi BTS 4G Tahun 2023 - Natashya Millania Alcoryansyah; Sri Dewi Andayani; Edison Bonar Tua Hutapea (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
This study analyzes the crisis rhetoric strategies employed by Indonesia's Minister of Communication and Information Technology (Menkominfo), Johnny G. Plate, in responding to the communication crisis surrounding the alleged corruption in the procurement of Base Transceiver Station (BTS) 4G Bakti Kominfo in 2023. Using Robert N. Entman's framing analysis framework, this research examines how three major Indonesian online media outlets, namely Kompas.com, Tempo.co, and CNN Indonesia, framed the official's public statements. A qualitative framing analysis was applied to news articles published from March to May 2023. The findings reveal significant differences in framing across the three media outlets. Kompas.com tended toward balanced framing, Tempo.co adopted a critical and investigative approach, while CNN Indonesia emphasized dramatic elements and social impact. The dominant rhetorical strategies identified include apologia, issue deflection, and victim narrative construction. This study contributes to understanding the relationship between crisis rhetoric, media framing, and public opinion formation in Indonesia.